2020
DOI: 10.1007/s00415-020-10288-6
|View full text |Cite
|
Sign up to set email alerts
|

Consciously processing balance leads to distorted perceptions of instability in older adults

Abstract: Background Persistent dizziness without a clear cause is common in older adults. We explored whether an anxiety-driven preoccupation with consciously processing balance may underpin the distorted perceptions of unsteadiness that characterises ‘unexplained’ dizziness in older adults. Methods We experimentally induced anxiety about losing one’s balance (through a postural threat manipulation) in a cohort of asymptomatic older adults and evaluated associated changes in perceived stability, conscious movement pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 41 publications
4
35
4
Order By: Relevance
“…Participants who expected that they would perform poorly perceived themselves to be more unstable than those who expected that they would perform well-irrespective of actual performance (i.e., objective postural stability). Given that numerous clinical balance disorders are characterized by distorted perceptions of instability [whereby actual and perceived stability are decoupled (Ellmers et al, 2021)], these novel findings have high levels of applied relevance. Future work should explore if such distortions of perceived instability can be altered through targeting faulty expectancies about balance performance.…”
Section: Subjective Postural Stabilitymentioning
confidence: 99%
“…Participants who expected that they would perform poorly perceived themselves to be more unstable than those who expected that they would perform well-irrespective of actual performance (i.e., objective postural stability). Given that numerous clinical balance disorders are characterized by distorted perceptions of instability [whereby actual and perceived stability are decoupled (Ellmers et al, 2021)], these novel findings have high levels of applied relevance. Future work should explore if such distortions of perceived instability can be altered through targeting faulty expectancies about balance performance.…”
Section: Subjective Postural Stabilitymentioning
confidence: 99%
“…The FSST-VR is a complex balance task, requiring increased awareness of body location and orientation, as well as planning complex directional changes. It has been shown that when facing an anxiety-inducing postural threat, high attention to selfmovement predicts subjective perception of instability in healthy older individuals under normal visual conditions [43]. It may be that people with PPPD and high trait anxiety, when faced with high visual loads, are worried of losing their balance, therefore freeze degrees of freedom and as a result limit spatial ROM during the task.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, of relevance is a recent study that has found that experimentally‐induced anxiety leads to distorted perceptions of subjective instability (Ellmers et al., 2021), which may lead us back to adopting over all "rigid" postural behavior.…”
Section: Discussionmentioning
confidence: 99%